Pengaruh Digital Marketing dan Personal Selling Terhadap Keputusan Pembelian Polis Asuransi Umum di PT. Askrindo Cabang Sorong - Retno Dewi Wijiastuti; Indriyani Hamzah (Transformasi: Journal of Economics and Business Management, 2023)
This study aims to determine the influence of Digital Marketing and Personal Selling to Decision Purchasing Insurance Policy PT. Askrindo Sorong Branch. This study has two independen variables is Digital Marketing and Personal Selling, while the dependent variable is Decision Purchasing The method used in this research is quantitative method with descriptive approach using data analisys, namely multiple linear regression analysis. Data were obtained by questioners that spread out to 60 customers of PT. Askrindo Sorong Branch which purchasing insurance policy (especially on Fire Insurance Policies). The sampling technique in this study is to purposive sampling approach. The result of the study concluded that Digital Marketing and Personal Selling partially and simultaneously had an effect on Decision Purchasing. The test results showed that the Personal Selling was the most dominant in this study. The coefficient of determination (R2) is equal to 0.283 or 28,3% the independent variables of digital marketing and personal selling affect a 28,3% on the dependent variable. While for the rest, 71,7% influenced or explained by other variabels not include in this study.